(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Cardiology Center of E Hospital is currently one of the leading facilities in the field of cardiovascular treatment. Every year, the center examines and treats thousands of patients from across the country, of which heart falilure accounts for a large number. This study aims to assess the nutritional status and related factors in patients with heart failureat the Cardiology Center of E Hospital in 2023-2024. Research methods: This is a cross-sectional study conducted on 110 in patients with heart failure at the Cardiology Center of E Hospital, aged from 18 to 65. Research variables included age, gender, and education level serum albumin, NYHA heart failure classification; and nutritional status assessed through BMI and SGA. Results: 49.1% of patients were at mild to moderate risk of malnutrition (SGA-B), and 8.2% were at severe risk of malnutrition (SGA-C), while 42.7% were not at risk of malnutrition (SGA-A). The prevalence of underweight patients was 20%, overweight patients was 21.8%, and obesity was 7.3%, according to BMI classification. The overweight/obese group had a 0.3 times lower risk of malnutrition than the normal group (95% confidence interval 0.1-0.6), and the group with albumin levels below 35 g/l had a 13.1 times higher risk of malnutrition compared to the normal group (p < 0,05). Conclusion: The study underscores the importance of assessing nutritional status to enhance treatment effectiveness and improve the health condition of heart failure patients.